Salvia miltiorrhiza in cancer: Potential role in regulating MicroRNAs and epigenetic enzymes - Lu, Meng; Lan, Xintian; Wu, Xi; Fang, Xiaoxue; Zhang, Yegang; Luo, Haoming; Gao, Wenyi; Wu, Donglu (Frontiers in Pharmacology, 2022)
MicroRNAs are small non-coding RNAs that play important roles in gene regulation by influencing the translation and longevity of various target mRNAs and the expression of various target genes as well as by modifying histones and DNA methylation of promoter sites. Consequently, when dysregulated, microRNAs are involved in the development and progression of a variety of diseases, including cancer, by affecting cell growth, proliferation, differentiation, migration, and apoptosis. Preparations from the dried root and rhizome of Salvia miltiorrhiza Bge (Lamiaceae), also known as red sage or danshen, are widely used for treating cardiovascular diseases. Accumulating data suggest that certain bioactive constituents of this plant, particularly tanshinones, have broad antitumor effects by interfering with microRNAs and epigenetic enzymes. This paper reviews the evidence for the antineoplastic activities of S. miltiorrhiza constituents by causing or promoting cell cycle arrest, apoptosis, autophagy, epithelial-mesenchymal transition, angiogenesis, and epigenetic changes to provide an outlook on their future roles in the treatment of cancer, both alone and in combination with other modalities.